CRITICAL CHALLENGES IMPLEMENTATION OF 3D PRINTING TOWARD INDUSTRY REVOLUTION (IR) 4.0: FROM CONTRACTOR PERSPECTIVE - Mahmood, Malik Ridhuan; Yop Zain, Fairiz Miza; Saidin, Mohamad Tajudin; Zainuddin, Mohd Firdaus; Hussein, Edelin (Journal of Islamic, Social, Economics and Development, 2024)
Industry 4.0, often referred to as IR 4.0 (the fourth industrial revolution), is a term used to describe the current trend of automation and data exchange in manufacturing technologies. It represents a significant shift in the way goods are produced, and it involves the integration of digital technologies, artificial intelligence, the Internet of Things (IoT), 3D printing, cloud computing, and other emerging technologies into the manufacturing process. The goal of Industry 4.0 is to create more efficient, flexible, and responsive manufacturing processes, leading to increased productivity, reduced costs, and faster time-to-market for products. It has the potential to transform industries across the globe and is often seen as a key driver of economic growth and competitiveness in the digital age. The study aims to determine the challenges of 3D printing implementation towards industry 4.0 in Kuala Lumpur, Malaysia. A questionnaire survey was distributed to the contractor company, and 108 contactor Grade 7 were chosen to fulfil the study’s goal. Distribution of questionnaire techniques are used for data collection. Quantitative methods had been used and in order to achieve the research objectives and been analysed by using Statistical Package for Social Science (SPSS) version 26 software. The study identified the critical challenges on the implementation is regarding the cost, reduce job opportunities, high-skilled procedure, insufficient guideline, lack of experiences, and high technology. Hence, it is suggested that the government sector and private sector do the collaboration for the 3D printing implementation. Collaboration between public and private entities creates better and more effective public and private services and products particularly in solving the issues.